Pendekatan Life Cycle Assessment dalam Menurunkan Emisi Gas Rumah Kaca (GRK) pada Struktur Beton Gedung (Studi Kasus Proyek Pembangunan Toll Corridor Development Fase 2 dan 3 Taman Mini) - Kaylani, Malika; Handayani, Dewi (Center for Environmental Research, LPPM, Universitas Sebelas Maret, 2025)
The construction sector contributes significantly to greenhouse gas (GHG) emissions, mainly through concrete use. This study applies Life Cycle Assessment (LCA) to evaluate and reduce GHG emissions in concrete structures, using a case study of the Toll Corridor Development (TCD) Phase 2 and 3 at TMII. Emissions were calculated based on material volume and emission factors, including cement, aggregates, steel, water, and admixtures. The study explores four supplementary cementitious materials (SCMs)—fly ash, metakaolin, silica fume, and zeolite—as partial cement substitutes. Results show that SCMs effectively reduce GHG emissions, with metakaolin achieving the highest reduction at 76.14%. This study recommends broader use of LCA in material selection to support Sustainable Development Goals (SDGs) in construction.